Model Pemberdayaan Ekonomi Mualaf Oleh Lembaga Amil Zakat: Studi Kasus LAZ BMH Pada Mualaf Suku Tengger - Andika Ramadhanu; Tika Widiastuti (Jurnal Ekonomi Syariah Teori dan Terapan, 2017)
The study aims to understand the economic empowerment model of Muslim converts by amil zakat institution, taking what LAZ BMH has done to Tengger’s Muslim converts as study case. Using qualitative descriptive approach with study case, the data collected through interviews with empowerment manager of BMH, Tengger’s Muslim converts, and the preacher, direct participatory observation, as well as documentation. In validating the data, this study uses data triangulation technique before analyzing through data reduction, presentation, and conclusion. The results of this study indicate that BMH has a role in economic empowerment of Tengger’s Muslim converts. It could be seen through their resurgent Islamic rituals, still-good relationships with their neighbors, and their success in making ends meet. Not only economically empowered, Tengger’s Muslim converts also become religiously stronger.